Decoration of Carbon Nanotubes with Cerium (IV) Oxide - S. Ya. Brichka; I. B. Yanchuk; A. A. Konchits; S. P. Kolesnik; A. F. Yefanov; A. V. Brichka; M. T. Kartel (Хімія, фізика та технологія поверхні, 2011)
Cerium (IV) oxide (ceria) nanoparticles, 6–10 nm in size, supported on carbon nanotubes (CNTs) were prepared by a chemical reaction between Ce(NO3)3 and NaOH. The effective processing parameters of ceria particles size were discussed. CNTs/CeO2 hybrids were characterized by transmission electron microscopy (TEM), selected area electron diffraction (SAED), Raman and electron paramagnetic resonance (EPR) spectroscopy. SAED and Raman spectroscopy showed that the CeO2 particles had a cubic crystal structure. EMR spectroscopy showed two paramagnetic signals related to CNTs and a third one belonging to paramagnetic defects of CeO2.